(untitled) (International Journal of Scientific Research in Science and Technology, 2024)
Natural antioxidants are becoming more and more well-liked as health difficulties become more widely known. These substances are in charge of lowering oxidative stress in the human body and impeding autoxidation reactions in the food system. The objective of this review is to provide a clear understanding of antioxidants in terms of their classification, function in food processing, and methods of detection. The review also identifies a few commercially accessible antioxidants that are used in food processing.